Systems Biology and Systems Pharmacology of Thrombosis. (31st July 2014) - Sequeira, A.; Volpert, V.; Panteleev, M.A.; Sveshnikova, A.N.; Belyaev, A.V.; Nechipurenko, D.Y.; Gudich, I.; Obydenny, S.I.; Dovlatova, N.; Fox, S.C.; Holmuhamedov, E.L.
<x content-type="archive" xml:space="preserve">Abstract</x> Thrombus formation in flowing blood is a complex time- and space-dependent process of cell adhesion and fibrin gel formation controlled by huge intricate networks of biochemical reactions. This combination of complex biochemistry, non-Newtonian hydrodynamics, and transport processes makes thrombosis difficult to understand. That is why numerous attempts to use mathematical modeling for this purpose were undertaken during the last decade. In particular, recent years witnessed something of a transition from the "systems biology" to the "systems pharmacology/systems medicine" stage: computational modeling is being increasingly applied to practical problems such as drug development, investigation of particular events underlying disease, analysis of the mechanism(s) of drug's action, determining an optimal dosing protocols, etc. Here we review recent advances and challenges in our understanding of thrombus formation.